Neuroprotective Effect of Taohong Siwu Decoction on Cerebral Ischemia/Reperfusion Injury via Mitophagy-NLRP3 Inflammasome Pathway - Zhao-Jie Ji; Zhao-Jie Ji; Yun Shi; Xing Li; Rui Hou; Yu Yang; Zhu-Qing Liu; Zhu-Qing Liu; Xian-Chun Duan; Xian-Chun Duan; Qing Liu; Wei-Dong Chen; et al. (Frontiers Media S.A., 2022)
Objective: Globally, cerebral ischemia has been shown to be the second leading cause of death. Our previous studies have shown that Taohong Siwu Decoction (THSWD) exhibits obvious neuroprotective effects on cerebral ischemia/reperfusion (I/R) injury (CIRI). In this study, we further explored the modulatory effect of THSWD on mitochondrial autophagy in CIRI and the relationship between modulatory effect and NLRP3 inflammatory vesicle activation, so as to further explain the mechanism of neuroprotective effect of THSWD.Methods: Middle cerebral artery occlusion reperfusion (MCAO/R) model in rats was built to simulate I/R. Adult male SD rats (220-270 g) were randomly divided into the following four groups: the sham group, the MCAO/R group, the MCAO/R + THSWD group, and the MCAO/R + THSWD + Mitochondrial division inhibitor 1 (Mdivi-1) group. Neurological defect scores were used to evaluate neurological function. 2,3,5-Triphenyltetrazolium chloride (TTC) staining was conducted to measure cerebral infarct volume. Nissl staining, H&E staining and TUNEL staining were executed to detect ischemic cortical neuronal cell viability and apoptosis. Electron microscopy was used to observe the ultrastructural changes of mitochondria. Total Reactive Oxygen Species (ROS) in tissue were measured by fluorescence spectrophotometry, and the activation status of microglia was evaluated by Iba-1/CD16 immunofluorescence staining. The levels of mitophagy-related proteins (LC3, Parkin, PINK1), NLRP3 inflammasome-related proteins (NLRP3, ASC, Pro-caspase-1, Cleaved-caspase-1), and inflammatory cytokines (Pro-IL-18, Pro-IL-1β, IL-18, IL-1β) were evaluated by western blotting.Results: The studies showed that THSWD treatment alleviated cerebral infarction and neurological deficiencies. THSWD upregulated the expressions of autophagy markers (LC3-II/LC3-I and Beclin1) mitochondrial autophagy markers (Parkin and PINK1) after CIRI. Furthermore, THSWD treatment attenuated microglia activation and damage to mitochondrial structures, thereby reducing ROS production and NLRP3 inflammasome activation. In contrast, the mitochondrial autophagy inhibitor Mdivi-1 inhibited the above beneficial effects of THSWD.Conclusions: THSWD exhibits neuroprotective effects against MCAO/R in rats by enhancing mitochondrial autophagy and reducing NLRP3 inflammasome activation.